Thioredoxin, a master regulator of the tricarboxylic acid cycle in plant mitochondria - Daloso, Danilo M. (2015)
Plant mitochondria have a fully operational tricarboxylic acid (TCA) cycle that plays a central role in generating ATP and providing carbon skeletons for a range of biosynthetic processes in both heterotrophic and photosynthetic tissues. The cycle enzyme-encoding genes have been well characterized in terms of transcriptional and effector-mediated regulation and have also been subjected to reverse genetic analysis. However, despite this wealth of attention, a central question remains unanswered: "What regulates flux through this pathway in vivo?" Previous proteomic experiments with Arabidopsis discussed below have revealed that a number of mitochondrial enzymes, including members of the TCA cycle and affiliated pathways, harbor thioredoxin (TRX)-binding sites and are potentially redox-regulated. We have followed up on this possibility and found TRX to be a redox-sensitive mediator of TCA cycle flux. In this investigation, we first characterized, at the enzyme and metabolite levels, mutants of the mitochondrial TRX pathway in Arabidopsis: the NADP-TRX reductase a and b double mutant (ntra ntrb) and the mitochondrially located thioredoxin o1 (trxo1) mutant. These studies were followed by a comparative evaluation of the redistribution of isotopes when 13C-glucose, 13C-malate, or 13C-pyruvate was provided as a substrate to leaves of mutant or WT plants. In a complementary approach, we evaluated the in vitro activities of a range of TCA cycle and associated enzymes under varying redox states. The combined dataset suggests that TRX may deactivate both mitochondrial succinate dehydrogenase and fumarase and activate the cytosolic ATP-citrate lyase in vivo, acting as a direct regulator of carbon flow through the TCA cycle and providing a mechanism for the coordination of cellular function.